The use of proteomics in search of allele-specific proteins in (Allo)polyploid crops - Carpentier, Sebastien C. (Humana Press, 2020)
Most organisms are diploid, meaning they only have two copies of each chromosome (one set inherited from each parent). Polyploid organisms have more than two paired (homologous) sets of chromosomes. Many plant species are polyploid. Polyploid species cope better with stresses thanks to the redundancy in the chromosome copy number and dispose in this way a greater flexibility in gene expression. Allopolyploid species are polyploids that contain an alternative set of chromosomes by the cross of two (or more) species. Gene variants unique for a preferential phenotype are most probable candidate markers controlling the observed phenotype. Organ or tissue-specific silencing or overexpression of one parental homeolog is quite common. It is very challenging to find those tissue-specific gene variants. High-throughput proteomics is a successful method to discover them. This chapter proposes two possible workflows depending on the available resources and the knowledge of the species. An example is given for an AAB hybrid and an ABB hybrid. Allele-specific gene responses are picked up in this workflow as gene loci displaying genotype-specific differential expression that often have single amino acid polymorphisms. If the resources are sufficient, a genotype-specific mRNAseq database is recommended where a link is made to the allele-specific transcription levels. If the resources are limited, allele-specific proteins can be detected by the detection of genotype-specific peptides and the identification against existing genomics libraries of the parents.